Dåajmijes vuekie lea saemien vuekie - Kappfjell, Leena; Gaski, Harald (Novus forlag, 2018)
Håkan Rydving was the one who first made Sami researchers aware of Linda Tuhiwai Smith's groundbreaking book Decolonizing methoÂdologies. Much has been written, both before and after, about research on indigenous peoples' own terms. For years, Håkan himself had already practiced the principle of learning indigenous peoples' languages and returning the results of the research, so in many ways, Smith's book became a confirmation of the legitimacy of what Sami researchers were doing, and of the necessity of having good allies in the execution of this practice. This short essay presents a Sami variant of indigenous research, namely dåajmijes vuekie, which is a proper aesthetic based on Sami uses of concepts and Sami understanding of this aesthetic on our own terms. This aesthetic is part of a larger movement, which in an international indigenous peoples' discourse contributes to the merging of tradition and innovation through the revitalization, rethematizing, and academizing of knowledge crucial for a decent life in accordance with norms that implies "to walk in beauty." This aesthetic turns an oral culture's ways of being together into writing from an academic, ethical, and community responsive perspective. The essay is written on purpose in Southern Sami, Håkan's second language of the heart!